Time-frequency response analysis of monetary policy transmission - Lubos Hanus; Lukas Vacha (Charles University in Prague, Institute of Economic Studies (IES), 2018)
In our study, we consider a new approach to quantify the effects of economic shocks on monetary transmission. We analyse the widely known phenomenon of price puzzle in a time-varying environment using the frequency decomposition. We use the frequency response function to measure the power of shocks transferred to different economic cycles. Considering both time and frequency domains, we quantify the dynamics of shocks implied by monetary policy within an economic system. While studying the monetary policy transmission of the U.S., the empirical evidence shows that low-frequency cycles of output are prevalent and have positive transfers. Examination of the inflation reveals that the frequency responses vary significantly in time and alter the direction of transmission for all cyclical lengths.
Keywords: 330; cyclicality; frequency; economic systems; monetary policy